2020
DOI: 10.1038/s41598-020-61568-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgery versus observation for small angle intermittent exotropia

Abstract: in young children with small angle exotropia, making decisions for the individual patient whether to perform surgery or not, and choosing the optimal time for surgical intervention are quite difficult. We aimed to compare the long-term outcomes of small angle intermittent exotropia of 20 prism diopters (PD) or less after observation versus strabismus surgery. A retrospective study was performed on 164 patients aged 3 to 13 who underwent surgical intervention or observation with or without conservative manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Accordingly, the increased convergence will result in greater accommodation ( 14 ). Some studies have found that the binocular AF of patients with IXT is significantly lower than that of a control group, which is consistent with the results of this study ( 15 ).…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, the increased convergence will result in greater accommodation ( 14 ). Some studies have found that the binocular AF of patients with IXT is significantly lower than that of a control group, which is consistent with the results of this study ( 15 ).…”
Section: Discussionsupporting
confidence: 93%
“…Four patients complained of lateral incomitance and limitation of abduction at last follow up at 6th months. Jae Yun Sung et al [24] This study compared the surgical outcomes of patients who had surgical correction with patients who were just followed for a minimum of 2 years for small angle exotropia of 20 prism dioptres (PD) or less. There was no significant difference in the surgical success rate between the groups at the final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Fusional control was also assessed with repeated trials of the cover‐uncover test at distance. Fusional control of exodeviation was classified into three levels according to the frequency of manifest exodeviation and refixation capacity: good (exodeviation manifests only after the cover test and fusion restarts immediately without blinking or refixation), fair (blinks or refixation to control the exodeviation) and poor (exodeviation manifests spontaneously, occurs in natural environments without any form of fusion disruption and persists after blinking and refixation efforts) 19–21 . Furthermore, we investigated cases requiring strabismus surgery more than 1 year after their initial examination.…”
Section: Methodsmentioning
confidence: 99%